2002
DOI: 10.1111/1468-2389.00217
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Center Procedures: Cognitive Load During the Observation Phase

Abstract: This study explores the traditional procedure of observing assessment center exercises while taking notes vs. an alternative procedure where assessors merely observe and postpone note-taking until immediately after the exercise. The first procedure is considered to be cognitively demanding due to the requirement of simultaneous notetaking and observing. Also, dual task processing (concurrent observing and notetaking) is considered to be especially demanding for assessors without rating experience. The procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…However, managerial assessors also rated candidates with higher accuracy. Other studies found that psychologists outperformed non-psychologists only when the criterion-related validity of the interpersonal ratings made was examined (r ¼ .24 vs. r ¼ .09; Damitz, Manzey, Kleinmann, & Severin, 2003) and that experienced assessors yielded significantly higher accuracy than inexperienced assessors (Kolk, Born, Van Der Flier, & Olman, 2002). As a whole, these studies reveal that both types of assessors have their strengths and weaknesses, in support of the common practice of including a mix of experienced line managers and psychologists in the assessor team.…”
Section: Assessor Selectionmentioning
confidence: 54%
“…However, managerial assessors also rated candidates with higher accuracy. Other studies found that psychologists outperformed non-psychologists only when the criterion-related validity of the interpersonal ratings made was examined (r ¼ .24 vs. r ¼ .09; Damitz, Manzey, Kleinmann, & Severin, 2003) and that experienced assessors yielded significantly higher accuracy than inexperienced assessors (Kolk, Born, Van Der Flier, & Olman, 2002). As a whole, these studies reveal that both types of assessors have their strengths and weaknesses, in support of the common practice of including a mix of experienced line managers and psychologists in the assessor team.…”
Section: Assessor Selectionmentioning
confidence: 54%
“…It seems reasonable to assume that taking notes while conducting an interview, when attention is divided, will result in quite different notes than after the interview, when investigators can pay full attention but have to base their notes on memory. The former task is considered cognitively demanding because note-taking, question generation, and listening to interviewee responses are all occurring simultaneously (Kolk, Born, van der Flier, & Olman, 2002). Additionally, the interviewer's attention has to shift from listening and writing down witness information to generating follow-up questions to elicit additional witness information.…”
Section: Notes From Investigative Interviewsmentioning
confidence: 99%
“…Note-taking may help to facilitate storage of witness information in working and long-term memory as interviewers must verbally record witness responses rather than passively listen, which in turn may lead to more accurate reports at a subsequent time. However, taking notes during interviews may be a mixed blessing as it may come at the expense of question generation and encoding witness responses (Kolk et al, 2002).…”
Section: Notes From Investigative Interviewsmentioning
confidence: 99%
“…Although there are other techniques used for selection in Turkey, the authors believe that judging all of the selection techniques at once will unduly load the perceptions of the raters and therefore result in possible rating errors (Kolk, Born, Van Der Flier, & Olman, 2002). Therefore, we decided to choose among the most valid, common and easy to use selection techniques: namely, interview, personality, and science achievement tests.…”
Section: Fairness Perceptions Of Selection Instruments and Goal Orienmentioning
confidence: 99%